Pengaruh Penggunaan Alat Evaluasi Sikap Terhadap Hasil Belajar Afektif Siswa Pada Mata Pelajaran Akidah Akhlak - Maria, Anly; Indriyani, Nida (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Affective issues are considered crucial by everyone, yet their implementation remains inadequate. This is due to the complexity of designing affective learning objectives compared to cognitive ones. An evaluation tool is deemed effective if it can assess something with outcomes that reflect the evaluated state. One of the reasons for the lack of attention to affective assessment implementation is the absence of clear affective evaluation tools. The objective of this research is to describe the influence of using attitude assessment tools in the Akidah Akhlak subject on students' affective learning outcomes in Class XI IPS 2 at MA Al-Ashdariyah Pakenjeng Garut. Thus, it aims to determine the extent of influence between attitude assessment tools in the Akidah Akhlak subject (Variable X) and students' affective learning outcomes (Variable Y). This study adopts a quantitative descriptive approach. Data collection methods include observation, documentary study, and distribution of questionnaires to 25 sampled students. Data analysis is conducted through statistical data analysis. The research findings indicate that the use of attitude assessment tools yielded an average score of 1.68, falling within the range of 1.01-5.00, classified as "Very Good." This suggests an improvement in students' attitudes following the use of these assessment tools in the Akidah Akhlak subject. Meanwhile, students' affective learning outcomes averaged 1.6, falling within the range of 1.01-5.00, also classified as "Very Good." This demonstrates that using attitude assessment tools is an effective solution to enhance students' affective learning outcomes. Based on statistical analysis, there is a significant influence (72.3785%) of attitude assessment tool usage on affective learning outcomes, while 27.6215% is influenced by other factors not examined in this study.  Keywords: Evaluation Tool, Affective Domain, Akidah Akhlak Subject